PENGARUH KONSELING REALITA UNTUK MENINGKATKAN PENGAMBILAN KARIR SISWA KELAS XII DI SMKN 1 TALIWANG KABUPATEN SUMBAWA BARAT TAHUN PELAJARAN 2020/2021 - Yayu Purwati, Suharyani, dan Diah Lukitasari (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2021)
Reality counseling is an approach that considers that realization to grow in order to satisfy the needs. Reality therapy is a system focused on behavior now. The problem in this study is the influence of reality counseling to improve the career taking of students of class XII SMKN 1 Taliwang West Sumbawa District Academic Year 2020/2021. The purpose of this study is to find out the influence of reality counseling to improve the career taking of students of class XII SMKN 1 Taliwang West Sumbawa School Year 2020/2021. The sample used in this study was 29 students. Instruments used in collecting data are questionnaire methods as the main method, while interview, observation and documentation methods as complementary methods. In this case the questionnaire is developed in indicators of career retrieval. Analyze the data using the t-test test. In accordance with the results of the analysis with a significant level of 5% it turns out that the value of